Management News and Notes (Academy of Management Journal, 1966)
The article presents Academy of Management news, including regional division updates as well as organizational and institutional happenings. The Eastern Division of the Academy of Management will meet on May 13th and 14th at the University of Maryland at College Park. Georgia State College has broken ground on their School of Business Administration building. Tulane University will offer a Ph.D. in Business Administration beginning September, 1966. Additional news about members is noted.